Modulation of Macrophage Efferocytosis in Inflammation - Korns, Darlynn R.; Frasch, S. C.; Fernandez-Boyanapalli, Ruby; Henson, Peter M.; Bratton, Donna L. (Frontiers in Immunology, 2011)
A critical function of macrophages within the inflammatory milieu is the removal of dying cells by a specialized phagocytic process called efferocytosis (“to carry to the grave”). Through specific receptor engagement and induction of downstream signaling, efferocytosing macrophages promote resolution of inflammation by i) efficiently engulfing dying cells, thus avoiding cellular disruption and release of inflammatory contents, and ii) producing anti-inflammatory mediators such as IL-10 and TGF-β that dampen pro-inflammatory responses. Evidence suggests that plasticity in macrophage programming, in response to changing environmental cues, modulates efferocytic capability. Essential to programming for enhanced efferocytosis is activation of the nuclear receptors PPARγ, PPARδ, LXR and possibly RXRα. Additionally, a number of signals in the inflammatory milieu, including those from dying cells themselves, can influence efferocytic efficacy either by acting as immediate inhibitors/enhancers or by altering macrophage programming for longer-term effects. Importantly, sustained inflammatory programming of macrophages can lead to defective apoptotic cell clearance and is associated with development of autoimmunity and other chronic inflammatory disorders. This review summarizes the current knowledge of the multiple factors that modulate macrophage efferocytic ability and highlights emerging therapeutic targets with significant potential for limiting chronic inflammation.